The Effect of Income Taxation on Labor Supply when Deductions are Endogenous - Triest, Robert K. (The Review of Economics and Statistics, 1992)
This paper extends the standard static model of labor supply and taxation to the case where people are able to legally avoid taxes through the use of itemized deductions. Tax deductible expenditures are treated as a Hicksian composite good with a price (for those who decide to itemize) proportional to one minus the marginal tax rate. Estimation of the commonly used linear labor supply model (extended to incorporate the additional composite good) on a cross-section of prime aged married men suggests that tax deductible consumption is an uncompensated substitute for leisure (and complement with labor). The impact of taxes through the relative price of deductible expenditures appears to be much stronger than through the net wage. Copyright 1992 by MIT Press.